Pengembangan Model Sistem Pencetakan Online Berbasis Web - Diyurman Gea (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Work efficiency and service quality improvement are two important things in competing with other businesses. Keep costs as low as possible with a satisfactory quality of service, can be optimized through the use of technology. One type of business that has the potential to be improved quality of service is a document copying services as implemented in Binus University. In addition to the staff and lecturers, students need the service for various types of documents such as copying lecture materials and other administrative documents. By leveraging the technology capabilities possessed by a photocopy machine to connect to a network computer, a system that supports the printing of documents through the Internet can be made. The online printing system is web-based, and capable of storing printing information into a database, so records can provide tracking information, which affects the quality of service and good performance.